MEMAKNAI KONFLIK DALAM PERSPEKTIF SOSIOLOGI MELALUI PENDEKATAN KONFLIK FUNGSIONAL - Muhammad Syawaludin (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2014)
Abstract: The term conflict comes from the Latin verb configere meaning “hit” each other. In the process development, the word configere adopted into the English language, that is conflict, which adopted also in the Indonesian language, meaning konflik. Experts have suggested a variety of definitions of conflict, the definition has different terms although essentially the meanings are the same. This is caused a conflict of meaning expressed from different scientific perspectives. Keywords: -conflict,- dyadic,- claim,- lawsuit